Manipontonia gen. nov., a new pontoniine shrimp genus for Periclimenes psamathe (De Man) (Crustacea: Decapoda: Palaemonidae) - Bruce, A. J.; Okuno, J.; Li, Xinzheng (Zootaxa, 2005)
A new genus, Manipontonia, is designated to include Periclimenes psamathe (De Man, 1902), on account of its peculiar morphology, with the combination of a long and slender rostrum with ventral margin unarmed, the proximal rostral dorsal teeth and epigastric tooth having fine ventral denticulations and endopod of male first pleopod with the appendix interna terminally with few terminal cincinnuli, which distinguishes this genus from all other species of Periclimenes, and the other genera of the Pontoniinae. The report includes some new host records: Acabaria robusta (Shann) [Gorgonacea]; Dendronephthya cf. decussata Utinomi [Alcyonacea].